IMPLEMENTASI PEMBANGUNAN INFRASTRUKTUR DALAM RANGKA PERCEPATAN PEMBANGUNAN DAERAH DI KECAMATAN SEKOLAQ DARAT KABUPATEN KUTAI BARAT - Jimmy Herman (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research aims to describe and analyse the implementation of infrastructure development in order to accelerate development in district of Sekolaq Darat Sub Province of Kutai Barat. Theresult foundthat theimplementation development of infrastructure in order to acceleration of development area in district of Sekolaq Darat was effective. Result of the development have succesfully adding 80 percent facilities and basic facilities in area. This performance was not reached final goals 100 percent because of limitation of budget allocation. This factor was main resistor factor of development infarstructure in Sekolaq Darat.